THE ROLE OF CUSTOMER ENGAGEMENT ON CUSTOMER LOYALTY: A STUDY AT A PRIVATE HIGHER EDUCATION INSTITUTION - Cynthia Ayu Manggarani (Faculty of Economics and Business, Hasanuddin University, 2018)
Today, consumers are no longer merely passive recipients of services provided by companies. Consumer's pervasiveness in their service consumption is the embodiment of Goods-Dominant Logic into Service-Dominant Logic paradigm shift. With this shift, consumers are now have the potential to be an effective corporate marketing agent. Private university, as the provider of education services whose survival depends on student participation and funding, is expected to be able to implement the right strategy in the face of the paradigm shift. This study aims to examine the effect of student engagement on student satisfaction. The effect of student satisfaction was then examined on student loyalty. The respondents of 140 students and former students of STIA Al Fithrah in Surabaya became the sample of this study. The results showed that student engagement has an important role to the development of student loyalty.